Antioxidant activity and cytotoxicity property of extracts from various coastal plants against HepG2 cell lines - Leong Kai Vyn; Murni Nur Islamiah Kassim; Desy Fitrya Syamsumir; Hermansyah Amir; Ismiyarto; Yosie Andriani (Institut Teknologi Bandung, 2020)
Reports have shown an upward trend for liver cancer in recent years. It is also one of the deadliest cancers globally due to its complexity in detection and treatment. Hence, there is an urgency todevelop the anti-liver cancer agent from natural resources which is highly effective with minimum side effects. This study aimed to evaluate the antioxidant activity and cytotoxicity property of extracts with different polarity solvents (hexane and methanol) obtained from coastal plants collected from Merang, Terengganu. Three species (Melaleuca leucadendra, Terminalia catappa, and Rhodomyrtus tomentosa) were chosen due to their abundance and lacking anticancer studies performed on them. Green leaves were collected directly from the trees and extracted using hexane and methanol successively. Preliminary phytochemical tests (phenolic, flavonoid, terpenoid, saponin, alkaloid and glycoside) were performed on the extracts, followed by an antioxidant test based on 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. Methanol extracts with high antioxidant property were continued for cytotoxicity study on HepG2 cell lines by 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The results showed that all methanol extracts from all plants showed high antioxidant property (IC50: 0.83-1.62 mg/ml) and moderately cytotoxic activity (IC50: 24.7-28 μg/ml) against HepG2 cell lines. In contrast, hexane extracts showed very weak antioxidant activities. The highest activity was obtained by methanol extract of M. leucadendra (MLM), followed by T. catappa (TCM) and R. tomentosa (RTM), respectively. These promising results indicated that MLM could be a potential candidate for further study related to the antioxidant and cytotoxicity on HepG2 cell lines, such as for anti-liver cancer agent.